2006
DOI: 10.1124/mol.105.019653
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Nuclear Factor-κB Inhibitory Effects of the Cell-Penetrating Penetratin Peptide

Abstract: Penetratin is a cationic cell-penetrating peptide that has been frequently used for the intracellular delivery of polar bioactive compounds. Recent studies have just revealed the major role of polyanionic membrane proteoglycans and cholesterol-enriched lipid rafts in the uptake of the peptide. Both proteoglycans and lipid-rafts influence inflammatory processes by binding a wide array of proinflammatory mediators; thus, we decided to analyze the effect of penetratin on in vitro and in vivo inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although penetratin peptide has been shown to suppress the infl ammatory response by inhibiting activation and nuclear translocation of nuclear factor-κB (Letoha et al, 2006) in rats, its specifi c immunogenic response is not known. Recently Moschos et al (2007) have used penetratin to deliver small-interfering RNA (siRNA) in lung and shown that siRNA-penetratin conjugate bring forth innate immune response by inducing TNF-α, IFN-α and IL-12 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although penetratin peptide has been shown to suppress the infl ammatory response by inhibiting activation and nuclear translocation of nuclear factor-κB (Letoha et al, 2006) in rats, its specifi c immunogenic response is not known. Recently Moschos et al (2007) have used penetratin to deliver small-interfering RNA (siRNA) in lung and shown that siRNA-penetratin conjugate bring forth innate immune response by inducing TNF-α, IFN-α and IL-12 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Letoha et al 49 50 described the effects of a novel cell-permeable NF-κB inhibitor. The NLS of the NF-κB p50 subunit was conjugated to the cell-penetrating penetratin peptide.…”
Section: The Effects Of Inhibiting Nf-κb Activation In Experimental Mmentioning
confidence: 99%
“…Changes in gene expression related to inflammation, oxidative stress, and secretion of pro-inflammatory cytokines may allow one to gain insight into the safety of drugs or excipients upon interaction with the respiratory epithelium. Also the activation of NF-κB, a transcription factor mediating inflammatory responses, may serve as an indicator for such events [34].…”
Section: In Vitro Models Based On Cells and Reconstructed Tissuesmentioning
confidence: 99%